“Desarrollo de una aplicación móvil para el monitoreo de pacientes con hipertensión arterial utilizando la tecnología ESP32” - Julio Vinicio, Sanaguano Santos (2020)
The evolution of information and communication technologies has revolutionized all fields of study, including health areas. This situation has given rise to telemedicine that is used to perform telediagnosis, teleconsultations, teleconferences, telehealth, and digital storage of medical documents. According to the World Health Organization (WHO), the development of Health mobile applications is directly or indirectly aimed to improve health behaviors, quality of life, and people's well-being. According to mHealth App Economics 2017/2018, the market size is considerable for the development of mHealth applications that are intended for the treatment of cardiovascular diseases and hypertension compared to diabetes, depression, and obesity diseases. This research work aims to develop a web / mobile application in the field of telemedicine to provide real-time ambulatory medical assistance to patients with hypertension. For this reason, medical records of some patients were reviewed to collect the blood pressure data, and the respective emulation was performed by means of a regression analysis. In Chapter I, a review of the literature extracted from journals, e-Books, theses, web pages specialized in topics related to web and mobile applications used in real-time patient monitoring was performed. In Chapter II, Boehm's spiral model was used for the development of the web / mobile application for monitoring patients with hypertension. The model establishes in the stages of development evaluations and improvements in the functionalities of the software. In Chapter III, once the development of the web / mobile application was completed, the real-time data emulation of blood pressure was performed, in addition to the ISO 9241-11 standard for the evaluation of usability criteria. Keywords: Mobile applications, ESP32 module, hypertension, telemedicine, blood pressure monitoring.